The relationship between work-life balance and job satisfaction among support staff in Jabatan Imigresen Malaysia Negeri Sarawak / Siti Nur Fatanah Mohd Hanipiah - Mohd Hanipiah, Siti Nur Fatanah (2018)
The core purpose for this study is to investigate the relationship between Work-Life Balance and Job Satisfaction among support staff in Jabatan Imigresen Malaysia Negeri Sarawak. Factors of Work-life Balance in this study include Working Hours, Working Conditions and Work Pressure. This study was conducted using convenience sampling and data was collected using questionnaires adapted from Fareez (2015), Work-Life Balance: The Impact of Family-Friendly Policies on Employees’ Job Satisfaction and Turnover Intention among Malaysian Organizations Culture and Kluczyk (2013), The Impact of Work- life Balance on The Wellbeing of Employees in The Private Sector in Ireland. The total of distributed questionnaires was 118 and they were collected back with all questions answered by the respondents. The questionnaire was analyzed by using Statistical Package for the Social Sciences (SPSS) Version 20. The result indicated in this study shows that there is a high, positive, and significant relationship between Working Hours and Job Satisfaction (r=.668, n=118 p<0.01). For the second variable, there is also a high, positive and significant relationship between Working Conditions and Job Satisfaction (r=.736, n=118, p<0.01). However, the third variable shows the result that there is a low, negative and significant relationship between Work Pressure and Job Satisfaction (r=-.092, n=118, p<0.05). Therefore, the overall results from this study show that all factors of Work-life Balance have a significant relationship towards Job Satisfaction.